Penerapan Konseling Individu Dengan Teknik Thought Stopping Dalam Mengatasi Kecanduan K-Pop - Relita, Liah; Razzaq, Abdur; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Kpop addiction is against Islamic teachings. Kpop addiction can cause a person to be too excessive or obsessed with the idol they like. To find out the description of K-Pop addiction in client "N", to find out what factors cause K-Pop addiction in client "N" and to find out the application of individual counseling with thought stopping techniques in overcoming K-Pop addiction in client "N". This research approach is a qualitative approach with a case study method. Subjects in the study are clients "N". Data collection techniques used are observation, interviews and documentation. Data analysis techniques include pattern matching, explanation, and time series analysis. The results of this study indicate that the picture of K-pop addiction on client "N" begins to follow his idol's style such as when posing for photos, knowing the names of favorite Korean boyband and girlband members, more Korean music than Indonesian music on cellphone playlists, knowing all the information on his idols. , fantasizing that his idol is his partner, and gets jealous easily. The factors that cause K-pop addiction to client "N" are from an uncontrolled environment, influence from friends, self-desire, and boredom at home. The implementation of individual counseling with the thought stopping technique is carried out in three stages, namely the initial stage, the middle stage, and the final stage. Counseling provided in 6 meetings can overcome K-pop addiction to client "N" in Sukajadi Village. He is no longer jealous, no longer hysterical when he sees his idol on social media, no longer watches videos of his idol, no longer considers his idol as a partner and has started doing things positive things like watching lectures.